The Correlation of Cognitive Flexibility with Pain Intensity and Magnitude of Disability in Upper Extremity Illness - Hageman, Michiel G.J.S.; Briet, Jan Paul; Oosterhoff, Thijs C.H.; Bot, Arjan G.; Ring, David; Vranceanu, Ana-Maria (Journal of Hand and Microsurgery, 2014)
Cognitive flexibility – the ability to restructure one’s knowledge, incorporate new facts, widen perspective, and adapt to the demands of new and unexpected conditions – can help one adapt to illness. The aim of this study was to assess the relationship between cognitive flexibility and hand and upper extremity specific disability in patients presenting to a hand surgeon. Secondarily, we determined predictors of cognitive flexibility and pain. Eighty-nine consecutive outpatients completed the Cognitive flexibility questionnaire (CFS), Short Health Anxiety Inventory-5 (SHAI-5), Pain Self-Efficacy Questionnaire (PSEQ), Disabilities of Arm, Shoulder and Hand, short form (QuickDASH), and Patient Health Questionnaire for Depression-2 (PHQ-2) in a cross-sectional study. CFS did not correlate with disability or pain intensity. Disability correlated with PSEQ (r=–0.66, p<0.01), PHQ-2 (r=0.38, p=<0.01), and SHAI-5 (r=0.33, p<0.01). Pain intensity correlated with PSEQ (r=–0.51 p<0.01) and PHQ-2 (r=0.41 p<0.01). There was a small correlation between the CFS and PSEQ (r=0.25, p=0.02). The best multivariable models for QuickDASH and pain intensity included PSEQ and PHQ and explained 35 % and 28 % of the variability respectively. Upper extremity specific disability and pain intensity are limited more by self-efficacy than cognitive flexibility. Interventions to improve self-efficacy might help patients with upper extremity illness.
Keywords: Cognitive flexibility scale; Pain intensity; Disability; Upper extremity; Self-efficacy